Sexuality education as a collective responsibility: a new health education curriculum in Cyprus - Ioannou, Soula; Kouta, Christiana; Constantinidou, Maria; Ellina, Panayiota (My University, 2014)
The development of health promotion is typically viewed as a reaction against both the excessive responsibility placed on individuals concerning their health-related choices and the absence of recognition of environmental factors associated with personal decision making. What though does sexuality education mean from the perspective of health promotion? According to one approach, it implies the existence of a curriculum that recognises the environmental factors affecting sexuality and sexual behaviour. It also suggests a curriculum that aims to empower students to engage with risky sexual behaviour, not just as a personal issue but also as a social matter. The emphasis is placed not merely on developing personal knowledge and skills associated with sexuality and sexual behaviour but on enabling active citizens to protect themselves and their co-citizens from sexual risks and to promote healthy sexuality. This paper discusses such a health promotion perspective in relation to the sexuality education curriculum as recently developed in Cyprus. It demonstrates how a health promotion perspective in relation to sex education can be translated into the establishment of learning objectives, appropriate pedagogic methods and the development of school materials. © 2014 © 2014 Taylor & Francis.
Keywords: Health promotion perspective; Schools; Sex education; Sexual health promotion